On Democracy and the Republic - Luo, Zhihao; Zhao, Changli (International Journal of Social Sciences and Public Administration, 2024)
In the modern political context, the terms democracy and republic are often regarded as synonyms and even confused. The apparent synonymity conceals the profound differences and rich connotations between the two in the history of political thought, so that the cognitive discussion of the relationship between democracy and republic has not yet reached a general consensus, although many views have been formed since the modern West. Through the examination of the terminological origin of democracy and republicanism and the temporal sorting of the relationship between the two, the study finds that, firstly, there exists a developmental logic of the relationship between democracy and republicanism in the spatial and temporal dimensions. In fact, the relationship between democracy and republicanism is complex and dynamic, full of historical processes of mutual influence and integration. Secondly, in the modern sense, democracy and republic are not in themselves one-dimensional concepts. The essence of republic is the structural state of power configuration, while the essence of democracy is the operational state of power utilization. It is precisely because the two are in different dimensions that the combination of power configuration and power operation makes the two inevitably intersect and become related.